High-speed tissue metabolism measurement using a combination of diffuse speckle contrast analysis and near-infrared spectroscopy - Chaebeom Yeo; Yeonhee Chang; Cheol Song (International Journal of Optomechatronics)
This study presents and validates a multimodal optical system combining diffuse speckle contrast analysis (DSCA) and near-infrared spectroscopy (NIRS) with a unique system design for high-speed tMRO2 monitoring. The optical system for simultaneous dual-wavelength illumination and detection by a single camera is constructed using dichroic mirrors without an external trigger device. Phantom experiments and in-vivo arterial occlusion tests are conducted by varying the camera exposure time from 0.5 ms to 10 ms to validate system performance. We analyze and compare the results according to the exposure time to acquire the optimal relative tMRO2 (rtMRO2) signal by dual-exposure time control. The in-vivo experiment confirmed that the relative blood flow (rBF) and tissue oxygenation index (TOI) signals from the two modalities had a trade-off with the camera exposure time. We obtained the optimal rtMRO2 using dual-exposure time control. We conclude that the proposed DSCA/NIRS provides real-time rtMRO2 assessment, which can provide biomarkers for diagnosing vascular diseases.